Hi everyone,

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

Hi everyone,

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

I think this turns into this:I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

I dont think this can be solved for M.